Implementation of Interactive Kahoot! Quizzes on Atomic Structure to Enhance Student Learning Motivation - Wahyu Hidayati; Nofri Yuhelman; Rahadian Zainul (SEARCH: Science Education Research Journal, 2026)
This study aims to describe the improvement of students' learning motivation in chemistry, specifically on the topic of atomic structure, through the implementation of a series of instructional improvements incorporating the educational game platform Kahoot!. The study was motivated by the low level of student motivation observed during chemistry lessons, both in individual and group activities, which was presumed to be caused by conventional, low-interaction teaching approaches. This research employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, comprising two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The subjects were 40 tenth-grade students at SMA Negeri 3 Padang. Data were collected using a learning motivation observation sheet designed to assess seven indicators of student motivation, including student engagement, initiative, communication, collaboration, information-seeking, and respect for peers' contributions. The collected data were analyzed descriptively using percentage calculations, with the results of each cycle used as a basis for reflection and refinement of actions in the subsequent cycle. The results showed an increase in the average percentage of student learning motivation from Cycle I to Cycle II, from 44.72% to 82.6%, exceeding the predetermined minimum target of 75%. This increase is attributed to the cumulative effect of the instructional improvements implemented in Cycle II, in which Kahoot! served as one component alongside increased teacher-student interaction and expanded opportunities for student participation. Based on the observation results across the two cycles, it can be concluded that the combination of these improvements, with Kahoot! as a key gamification element, was associated with an improvement in students' learning motivation in chemistry.